PENDIRIAN BADAN USAHA MILIK DESA (BUMDES) SEBAGAI PENOPANG PEREKONOMIAN MASYARAKAT DESA HOLIMOMBO MELALUI SOSIALISASI, PERAN SERTA MANFAAT - Ernawati Malik; Adriani Hasan, Waode; Asniar Ridzal, Nining; Tri Pratiwi, Endang; Mahmuda, Dewi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
BUMDes was established not only as a business entity, but also as a form of community empowerment to be able to manage the potential of the village either independently or sustainably. With the existence of BUMDes, village communities are encouraged to play an active role in all aspects of BUMDes management, from planning, implementation, to supervision, it is hoped that this will foster a sense of ownership and responsibility for economic progress in the village. This Community Service is carried out with the aim of socializing, the role and benefits of the importance of establishing BUMDes in Holimombo Village, Wabula District, Buton Regency. The methods used include lecture and discussion methods involving various parties, namely the Village Head and his staff, community leaders, representatives of residents from various elements. Holimombo Village has the opportunity to improve the welfare of its people through natural resources and tourism, the presence of BUMDes is important and is expected as a strategic effort in realizing village economic independence, increasing village original income (PADesa) and also helping to improve community welfare and reduce the gap in economic development in the village.